2023
DOI: 10.1186/s40795-023-00743-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of dietary intake amongst Black, Asian and other minority ethnic groups in high-income countries: a systematic review of qualitative literature

Abstract: Background Minority ethnic groups are a fast-growing population in many high-income countries, partly due to the increasing population of immigrants and second-generation migrants. The dietary practices of some of these minority ethnic groups might make them to be disproportionately affected by obesity and increase their risks of developing non-communicable diseases. Population-specific interventions and strategies are vital to addressing poor nutritional practices among this population. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Food-insecure shopping priorities might point to the importance of cost when grocery shopping and a limited access to healthy vegetables for consumption [ 45 ]. Studies have shown that cost might not be as much of a barrier as a vegan diet can reduce grocery shopping bills over USD 500 per year [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Food-insecure shopping priorities might point to the importance of cost when grocery shopping and a limited access to healthy vegetables for consumption [ 45 ]. Studies have shown that cost might not be as much of a barrier as a vegan diet can reduce grocery shopping bills over USD 500 per year [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no gainsaying the fact that effective communication is pivotal in health promotion. Poor communication with health workers and the entire health system is a common experience of migrants, especially those who are not native English speakers [ 27 , 28 ]. Thus, part of the barriers minoritised communities may face in adopting weight management practices could be language and cultural barriers, as the result of our study suggests.…”
Section: Discussionmentioning
confidence: 99%
“…Using a participant-oriented approach, requiring participants to share their own experiences using their own words [ 25 , 26 ], data was generated using semi-structured interviews [ 27 ] to explore motivators and barriers to weight management among twelve individuals, six males and six females. Notably, experience regarding weight management in this study did not only entail having engaged in weight reduction but also perceptions around weight management [ 27 , 28 ]. During the interviews, participants were asked some unidentifiable socio-demographic questions.…”
Section: Methodsmentioning
confidence: 99%